PENINGKATAN EKONOMI KELOMPOK WANITA TANI MELALUI PENGOLAHAN AMPAS KELAPA MENJADI PRODUK BERNILAI - Putra, I.G.A.K.; Wiadnyani, A.A.I.S.; Putra, I.N.K. (Buletin Udayana Mengabdi, 2024)
Ped Village is one of the villages located in Nusa Penida District, Klungkung Regency. The livelihood of most of the population is in agriculture, fisheries and tourism. One of the commodities being developed was coconut. One part of the coconut that has not been optimally utilized is coconut pulp, which is the waste of processed Virgin Coconut Oil (VCO) that has been produced by KWT Bodong Lestari. The aimed of this community service was to transfer appropriate technology and direct practice, especially the technology of processing coconut pulp into high-economic value products such as coconut pulp flour which is then processed into cookies and brownies. The implementation of this community service uses training methods and processing of coconut pulp into a high-economic value products accompanied by good packaging and labeling. The results of the activity were the creation and achievement of product innovations in the form of coconut pulp flour, cookies and brownies made from coconut pulp. Keywords: Brownies, Coconut Pulp, Cookies, Klungkung, Processing.